Role of Celebrity Image-Congruence in Predicting Travel Behaviour Intention - Joydeep Biswas; Shabbirhusain R.V. (ASEAN Journal on Hospitality and Tourism, 2022)
The objective of this research was to investigate how the perceived image congruence of the traveller influences the relationship between celebrity endorser attributes and travel behaviour intentions in the tourism context. 310 respondents were surveyed using online convenient sampling in India. Hypotheses were tested using structured equation modelling. The results suggest that endorser celebrity traits of physical attractiveness, trustworthiness, and expertise positively impact a tourist’s intention to revisit or recommend the endorsed destination. Additionally, greater image congruence between the celebrity endorser and the endorsed destination is likely to result in higher intention of the traveller to visit the destination. The study contributes to the existing body of academic literature by demonstrating the combined influence of celebrity characteristics and image congruence on the travel intentions of a tourist. This research benefits the practitioners by suggesting that destinations should focus on carving a messaging strategy focusing on how the destination image is consistent with how the targeted traveller perceives himself or herself with the messaging source being a celebrity who is either physically attractive, trustworthy or a travel expert.